Pendekatan Sosial Sukidi untuk Mempertahankan Dukungan Konstituen sebagai Anggota DPRD Tebo Tiga Periode 2009-2024 di Dapil Kabupaten Tebo - Syah, Harpin; Dison, Ronal; Sari, Tia Arum (Lembaga Teewan Journal Solutions, 2026)
This study aims to examine Sukidi's approach in maintaining constituent support as a member of the Tebo Regional People's Representative Council (DPRD Tebo) for three consecutive periods (2009-2024), representing Electoral District 3 of Tebo Regency (Rimbo Bujang-Rimbo Ulu). A qualitative method was employed, with informants selected through purposive sampling. The findings show that Sukidi maintained constituent support not only through a social approach but also through an economic approach. Given that contemporary society increasingly measures relationships in nominal terms, legislative candidates and members are required to remain active and responsive to community aspirations and needs. Based on these findings, it can be concluded that Sukidi's strategy in sustaining constituent support combines both social and economic approaches. Several inhibiting factors were also identified, including internal party obstacles, internal competition within villages or the electoral district, and funding limitations. The initiatives undertaken have generated positive insights and impacts for the community, particularly in Purwoharjo Village, although the outcomes are not yet fully optimal and certain shortcomings remain. This study contributes to a deeper understanding of constituency maintenance strategies employed by incumbent legislators in local politics.